KARAKTERISTIK MUTU DAN RENDEMEN ALGINAT DARI EKSTRAK RUMPUT LAUT Sargassum sp. DENGAN MENGGUNAKAN LARUTAN ASAM ASETAT - Topan Wira Aristya, I Made; Admadi, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This research is aimed to determine the concentration of acetic acid which is appropriate to produce high yield and best alginate quality of Sargassum sp. seaweed. This study uses descriptive quantitative and qualitative design by comparing the best results of the standard alginate exist. The concentrations of acetic acid tested are 0%; 0.5%; 1%; 1.5%; 2%; and 2.5%. Each concentration was repeated 3 times. The variables observed in the alginate include yield, moisture content, ash content, viscosity, pH, and the functional groups by FTIR. The extraction of alginate with a solution of acetic acid concentration by 1.5% is the best in the alginate extraction with 2.90% of yield, 7.37% moisture content, 0.37% ash content, 12cp viscosity, and a 6.0 of pH. In the other side also, the alcohol/phenol (OH) by the wave number of 3626.17 cm -1 , alkane group (C-H) by the wave number of 298.88 cm -1 , a triple bond (C?N) at wave number of 2376.30 cm -1 , carbonyl (C=O) on 1680.00 cm -1 wave numbers, and typical areas fingerprint mannuronat at wave number of 852.54 cm -1 were gained.   Keywords: alginate, extraction, Sargassum sp., acetic acid
Keywords: 132